2017
DOI: 10.3390/fi9020022
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Identifying the Mood States of Social Network Users Based on Cyber Psychometrics

Abstract: Analyzing people's opinions, attitudes, sentiments, and emotions based on user-generated content (UGC) is feasible for identifying the psychological characteristics of social network users. However, most studies focus on identifying the sentiments carried in the micro-blogging text and there is no ideal calculation method for users' real emotional states. In this study, the Profile of Mood State (POMS) is used to characterize users' real mood states and a regression model is built based on cyber psychometrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Researches in opinion mining and sentiment analysis indicated that a lexicon construction is the basis of users’ emotions and opinions recognition (Huang, Niu, & Shi, 2014). We introduced the lexicon construction method used in our previous study (Wang, Li, Huang, Liu, & Zhang, 2017) applied both semantic knowledge and Amazon corpus to construct an online lifestyles lexicon. First, we obtained seven seed words sets including dimensions like “Comfortable,” “Entertainment,” “Luxury,” “Tradition & Conservation,” “Rational,” “Fashion Sense,” and “Social Activities.” Second, we used the synsets in WordNet to extend the seed words.…”
Section: Methodsmentioning
confidence: 99%
“…Researches in opinion mining and sentiment analysis indicated that a lexicon construction is the basis of users’ emotions and opinions recognition (Huang, Niu, & Shi, 2014). We introduced the lexicon construction method used in our previous study (Wang, Li, Huang, Liu, & Zhang, 2017) applied both semantic knowledge and Amazon corpus to construct an online lifestyles lexicon. First, we obtained seven seed words sets including dimensions like “Comfortable,” “Entertainment,” “Luxury,” “Tradition & Conservation,” “Rational,” “Fashion Sense,” and “Social Activities.” Second, we used the synsets in WordNet to extend the seed words.…”
Section: Methodsmentioning
confidence: 99%
“…Lexicon is the basis for utilizing customer word use behaviors to automatically extract psychological traits. The combination of semantic knowledge and online corpora not only utilizes the semantic relationships as prior knowledge to provide accurate seed words but, also, help to foster the word association information, such as term position and word co-concurrency in the corpus [60]. Based on semantic knowledge and Amazon corpus, our research applies the NLP method to automatically construct SVS and BFF consumer psychographic lexicons for consumer value and personality identification.…”
Section: Word Use-based Psychographic Inferencementioning
confidence: 99%
“…Manual analysis, though attains highest precision ingests costs, time and resources. Lexicon analysis, on the other hand, espouses the automated evaluation of sentiment analysis and thus commonly accepted (Wang et al, 2017). When constructing a lexicon, firstly, seed words are generated, which then identifies the mood state of responses grounded on these seed words (Mantyla et al, 2017).…”
Section: Distinguishing Emotional Features Using Profile Of Mood Statmentioning
confidence: 99%